Early-Onset Depression in Stroke Patients: Effects on Unfavorable Outcome 5 Years Post-stroke - Zeng, Ya-Ying; Wu, Meng-Xuan; Zhou, Sheng-Nan; Geng, Dan-Dan; Cheng, Lin; Fan, Kai-Li; Yu, Xin; Tang, Wen-Jie; He, Jin-Cai (Frontiers in Psychiatry, 2021)
Background: Post-stroke depression (PSD) constitutes an essential complication of stroke and is associated with high-risk unfavorable outcome after stroke. The main objective of this prospective study was to determine the relationship between early-onset PSD (1 month after stroke) and functional outcomes 5 years after baseline enrollment. Methods: Four hundred thirty-six patients who met the criteria were included in this study from October 2013 to February 2015. The follow-up time for each patient was 5 years, with follow-up every 3 months. Patients received questionnaires including the 17-item Hamilton Depression Scale (HAMD), the Mini-Mental State Examination (MMSE), the National Institutes of Health Stroke Scale (NIHSS), the modified Rankin Scale (mRS), and the Barthel Index (BI). Results: Of the 436 patients, 154 (35.3%) patients with the prevalence of PSD status at baseline, 26 (7.2%) patients with the prevalence of PSD status, and 73 (20.1%) had an unfavorable outcome 5 years after stroke. The odds ratio (OR) for unfavorable outcome at 5 years in the PSD group was 2.2 relative to the non-PSD group after adjusting for potential risk factors [OR = 2.217, 95% confidence interval (CI) = 1.179–4.421, P = 0.015]. In the early-onset PSD group, HAMD scores were independently associated with 5-year unfavorable outcome rates (OR = 1.168, 95% CI = 1.015–1.345, P = 0.031). Conclusions: Our findings indicate that early-onset PSD status in Chinese patients is an independent risk factor for unfavorable outcome 5 years after stroke, and that the severity of PSD is also related to unfavorable outcome.